Orychophragvioline A, a Novel Alkaloid Isolated from Orychophragmus violaceus with Anti-Cervical Cancer Activity - Ya Li; Tonghe Liu; Guangjie Pan; Yihang Li; Guoxu Ma; Yong Hou; Nailiang Zhu; Xudong Xu (Molecules)
A new alkaloid (orychophragvioline A) and nine known compounds were yielded from the seeds of Orychophragmus violaceus. Their structures were determined by various spectroscopic techniques and single-crystal X-ray diffraction. Orychophragvioline A is a rare alkaloid with an unusual 1-methyl-4-phenyl-2,3-diketopiperazine skeleton connected with a guanidine group via an amide bond. The results of antitumor tests in vitro showed that it exhibited prominent cytotoxicity against Hela cells with an IC50 value of 11.95 ± 1.52 μM. Further investigations suggested that it significantly inhibited cellular proliferation, migration, and invasion in a dose-dependent manner, thus inducing the apoptosis of Hela cells. These findings indicate that orychophragvioline A can be regarded as a potential natural leading compound against cervical cancer.